Employee Engagement:The Role of Psychological Empowerment and Perceived Organizational Support - Krishnaveni, R.; Monica, R. (SFIMAR Research Review, 2015)
Employee engagement (EE) has been reigning as the success mantra in the workplace for nearly two and a half decades. With the changing technology and rapidly growing workforce, retaining and recruiting the best talent is the need of the hour EE when crafted well to meet the needs of the workforce can be dynamic in nature and bring about organizational effectiveness which in turn will lead to competitive advantage. Organizations at large, have adopted grand strategies to have an engaged workforce, because engaged employees contribute to the bottom line outcomes. In addition, having engaged employees is the overarching demand for organizations. Having this as the backdrop, this study emphasises the importance of EE and the drivers needed in the workplace to have an engaged workforce. Secondly, it propounds the role of psychological empowerment and perceived organizational support in levering employee engagement in the minds of employees.